(untitled) (Revista Venezolana de Salud Pública, 2021)
Burnout Syndrome is considered a global epidemic and a public health problem, characterized by emotional exhaustion, depersonalization, and reduced feelings of work-related personal accomplishment. The present study was based on an investigation which it determined the presence of Burnout Syndrome in medical students at the “Dr. José Francisco Molina Sierra” Hospital, between May 2018 - May 2019. It was carried out in an analytical matrix, based on the scientific method and non-experimental, cross-sectional design, located at the comparative and field-type level. Medical students were used as a population to study. The technique for data collection was the survey, and the instrument was the self-control test, the "Maslach Burnout Inventory", in the Colombian version. The Burnout Syndrome was present in 66% of medical students, with subscale values ​​of 69% for high level of emotional exhaustion, 47% for high level of depersonalization and reduced personal accomplishment with a low level of 53%.